2019
DOI: 10.1080/17457300.2019.1653930
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cyclists’ crashes: an analysis of routinely recorded crash data

Abstract: Previous research on gender differences in road crashes has focussed uniquely on car drivers and there has been little research examining such differences among cyclists. In this study, we investigated gender differences in bicycle crashes, using routinely recorded crash data. The present paper focussed on characteristics related to the type of crashes (type of collision and opponent vehicle), the infrastructure (road type and type of road segment), the environmental (season, road surface condition and weather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 65 publications
2
19
0
5
Order By: Relevance
“…This was observed for pedestrians as well as for cyclists. For cyclists, this may can be explained in possible differences in the type of bicycle they ride, their riding speed and the type of accidents they are involved in Boele-Vos et al (2017) , Fyhri et al (2019) , Prati et al (2019) . Male cyclists for example more often ride on racing bikes whereas (elderly) female cyclists more often ride on pedelecs (electrically assisted bicycles) ( Boele-Vos et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was observed for pedestrians as well as for cyclists. For cyclists, this may can be explained in possible differences in the type of bicycle they ride, their riding speed and the type of accidents they are involved in Boele-Vos et al (2017) , Fyhri et al (2019) , Prati et al (2019) . Male cyclists for example more often ride on racing bikes whereas (elderly) female cyclists more often ride on pedelecs (electrically assisted bicycles) ( Boele-Vos et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a 2019 UK study, a higher percentage of men participated in risk cycling behaviour resulting in more crashes compared to women regardless of age. 185 So cities must also consider how designs can account for men's perceptions of risk while encouraging cycling and outdoor physical activity.…”
Section: Poverty Gender and The Social Determinants Of Men's Healthmentioning
confidence: 99%
“…In the UK, in 2019, 6% of all road fatalities were people cycling [4], with socially patterned fatalities evident [6]. In Italy, cyclist fatalities largely involved people aged 65 years and above, occurred on urban roads, in collisions with cars with males more likely than females to be involved in a cycling crash [7] and more likely to be killed as a result [8]. However, research conducted in the Netherlands and Denmark found that females accounted for the majority of cycle-related deaths [3].…”
Section: Introductionmentioning
confidence: 99%